2019
DOI: 10.3389/fnins.2019.00696
|View full text |Cite
|
Sign up to set email alerts
|

Brain Modulatory Effects by Low-Intensity Transcranial Ultrasound Stimulation (TUS): A Systematic Review on Both Animal and Human Studies

Abstract: Background and objective: Low Intensity Transcranial Ultrasound Stimulation (TUS) is a new form of non-invasive brain modulation with promising data; however, systematic reviews on the brain modulatory effects of TUS on both animals and humans have not been well-conducted. We aimed to conduct a systematic review on the studies using the TUS to modulate the brain functions and associated behavioral changes in both animals and humans. Methods: A literature search for published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Furthermore, Yuan et al (2020) reported a monotonic dose-response parametric relationship with the cerebral blood flow peak value increasing as a function of stimulation intensity [0.20, 0.40, 0.80, and 1.10 W/cm 2 (I SPPA )] and SD (50, 100, 200, 300, and 400 ms), while DC (10, 20, 30, and 40%) only had a weak effect on peak response. These findings demonstrated the permutations of LI-TUS parameters that can manipulate modulatory function that is reflected as changes in the excitability of neuronal activity in M1 of healthy mice (Wang et al, 2019b).…”
Section: Neuromodulatory Effect Of Tus In Animalsmentioning
confidence: 72%
See 3 more Smart Citations
“…Furthermore, Yuan et al (2020) reported a monotonic dose-response parametric relationship with the cerebral blood flow peak value increasing as a function of stimulation intensity [0.20, 0.40, 0.80, and 1.10 W/cm 2 (I SPPA )] and SD (50, 100, 200, 300, and 400 ms), while DC (10, 20, 30, and 40%) only had a weak effect on peak response. These findings demonstrated the permutations of LI-TUS parameters that can manipulate modulatory function that is reflected as changes in the excitability of neuronal activity in M1 of healthy mice (Wang et al, 2019b).…”
Section: Neuromodulatory Effect Of Tus In Animalsmentioning
confidence: 72%
“…Language limitations were not imposed to ensure the inclusion of published manuscripts in other languages. In addition, two recently published systematic review articles were reviewed to exclude studies that already reviewed by Wang et al (2019b) and Di Biase et al (2019).…”
Section: Literature Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…TUS can be transmitted through the skull and may exert direct modulation of neurons at low intensities [ 2 , 3 , 4 ]. The putative mechanism of TUS relates to the mechanical energy of ultrasound, which produces changes in cell membrane proteins and bioelectrical properties, including activation of voltage-dependent sodium and potassium, and calcium channels [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%